Język psychozy: Dadaizm a teoria psychoanalityczna Wilfreda Ruprechta Biona - Szkudlarek, Joanna (Przestrzenie Teorii, 2019)
This paper juxtaposes W.R. Bion’s psychoanalytic theory of psychosis with Dadaistic works of art. The aim of this juxtaposition is to enable the reader to better understand Bion’s theory of psychosis and to propose a new approach to Dadaistic work from the perspective of psychoanalytic theory. The works of art will illustrate basic psychotic mechanisms. It is a starting point for further elaboration of Bion’s theory of thinking and his view on subjectivity. At the same time an original approach towards Dadaistic works of art will be presented, based on psychoanalytic concepts of fragmentation and symbolic equation. Essential differences between creativity and madness will be emphasized.